Performance and Economic Evaluation of Power Transformer - Muhammad, Sabo Sani; Abdulrazak, Sabo; Haruna, Y. S.; Abdulhafiz, Sabo; Nazif, D. M. (Darul Yasin Al Sys, 2025)
This study presents a comprehensive performance and economic evaluation of a three-phase 132/33 kV delta/star power transformer using an enhanced Finite Element Method (FEM) integrated with ANSYS Maxwell software. The transformer model, developed based on operational data from the Gudum substation in Bauchi, Nigeria, was designed to assess electromagnetic and thermal characteristics under no-load, full-load, and short-circuit conditions. The FEM simulation incorporated detailed geometric configuration, material properties (M125-027S laminated steel core and copper windings), optimized meshing, and coupling with external electrical circuits. Key performance indicators—including magnetic flux density, core and copper losses, voltage and current outputs, and efficiency—were evaluated under varying load scenarios. The model exhibited peak efficiency of 80.84% at 97.10% loading, and simulated load currents demonstrated loss reductions between 8.46% and 11.05% relative to empirical measurements, validating the model’s reliability. Furthermore, a life cycle cost (LCC) analysis was conducted using present-value cash flow techniques over a projected 22-year operational period. The total LCC was estimated at ₦2,777,811,381, with no-load and load losses accounting for ₦534.2 million and ₦1.88 billion, respectively. These findings underscore the substantial economic implications of design and material decisions in transformer manufacturing and operation. The study emphasizes the value of advanced FEM-based tools in optimizing transformer performance and cost-efficiency, offering strategic guidance for procurement, maintenance planning, and long-term infrastructure investment in power systems.